COMMUNITY KNOWLEDGE AND ATTITUDE TO RABIESIN IN THE BANJAR PEKANDELAN, BEDULU VILLAGE, BLAHBATUH DISTRICT, GIANYAR REGENCY - I Gede Arya Bayu Mahendra; I Wayan Masa Tenaya; Romy Muhammad Dary Mufa (Buletin Veteriner Udayana, 2024)
Rabies is known as Lyssa, hygrophobia or also mad dog disease which is caused by a virus from the genus Lyssavirus, family Rhabdoviridae which is acute and attacks the central nervous system. Rabies eradication does not only depend on the problem of dogs or other rabies-transmitting animals, but also involves human problems. This study aims to determine the knowledge and attitudes of the community about Rabies Disease in Banjar Pekandelan, Bedulu Village, Blahbatuh District, Gianyar Regency, Bali. There are 64 household heads in Banjar Pekandelan and 13 families who keep dogs. The design of this research is observational. The number of respondents in this study were all families who kept dogs in Banjar Pekandelan. Research data collection was carried out by interviewing the dog owner's family using a questionnaire. The data obtained from interviews regarding the knowledge and attitude aspects of the dog keeping community were tabulated using Ms. Excel, data were analyzed descriptively qualitatively and displayed in table form. From the research results, it was found that the community already ewell understood about rabies. While the attitude of the community is worth, which means that the community has a positive attitude in dealing with rabies in dogs. It can be concluded that the knowledge and attitude of the community in Banjar Pekandelan, Bedulu Village towards rabies is high and positive in dealing with rabies. So that it makes it easier to carry out the prevention and control of rabies there